Longitudinal Outcomes Following a Randomized Controlled Trial of Dynamic Splint Stretching for Carpal Tunnel Syndrome. (September 2016) - Willis, F. Buck; Fowler, Brook
Background: The incidence of carpal tunnel syndrome (CTS) is 48 million patients in the United States. The purpose of this longitudinal study was to determine whether Dynasplint stretching (immediately after diagnosis) had an effect on a patient's decision to seek surgical treatment for CTS.Methods: Fifty patients (10 men, 40 women, mean age 51.2 ± 12 years) were recruited for this randomized, controlled, longitudinal trial. Patients were diagnosed with CTS by physical examination and nerve conduction studies. The intervention used was Dynasplint stretching that delivered a prolonged duration of low load stretching. Patients who were randomly chosen for the Experimental category wore the device for two 30-minute sessions per day with regular increases in splint tension for 60 days. Control patients received nonsteroidal anti-inflammatory medication plus instructions on daily home stretching.Results: The final, longitudinal outcome showed a 72% reduction in surgery chosen by the experimental group (n = 25), compared with 38% reduction for control patients (n = 25).Conclusions: Immediate treatment with Dynasplint stretching showed a 2 to 1 reduction in surgery, with abundant financial savings.